MUHAMMADIYAH PRIMARY SCHOOL SANITATION DESCRIPTION IN SAWANGAN DEPOK 2018 - Ernyasih, Ernyasih; Srisantyorini, Triana (Muhammadiyah Medical Journal, 2020)
Background: Children are the next generation of the nation, so they need a healthy environment in order to work optimally and they spend more time at school so school sanitation is needed. School sanitation is an important element in efforts to improve the quality of education. Increased access to sanitation in schools can have a significant impact on improving the quality of students' health at school. Only around 11.43% of schools from all levels in Indonesia have separate and functioning latrines. Whereas an average of 52.49% of schools have inappropriate toilets, are not separate, or do not function. Muhammadiyah Primary School Sawangan, is one of the places of education where environmental health conditions are quite alarming and have a high risk of diarrhea. The purpose of this research is to know the description of school environmental sanitation in Muhammadiyah primary School Sawangan based on the Decree of the Minister of Health RI Number 1429/Menkes/SK/XII/2006. Methods: The research method used is descriptive qualitative approach. This research was conducted with an observation approach and in-depth interviews related to school sanitation facilities and informants were the Principal and janitor in November 2018. Conclusion: Based on the Decree of the Minister of Health RI No. 1429/Menkes/SK/XII/2006, clean water facilities at primary School Muhammadiyah, Sawangan are categorized as good, toilet facilities are not appropriate, SPAL facilities are appropriate, waste disposal facilities are not appropriate.